Angiopoietins and Tie2 in vascular inflammation. Issue 5 (September 2017) - Parikh, Samir M.
Abstract : Purpose of review: As a subset of the organism-wide reaction to severe infection, the host vascular response has received increasing attention in recent years. The transformation that small blood vessels undergo to facilitate the clearance of pathogens may become harmful to the host if it occurs too broadly or if it is sustained too long. Adverse clinical manifestations of leaky and inflamed blood vessels include edema impairing the function of critical organs and circulatory shock. Recent findings: The study suggests that this host vascular response may be both measurable and potentially targetable. Tie2 is a receptor tyrosine kinase (RTK) heavily enriched in the vascular endothelium whose tonic signaling actively maintains vascular quiescence. When Tie2 becomes inactivated, important molecular brakes are released in the endothelium, which in turn potentiate inflammation and vascular leakage. The ligands of Tie2, Angiopoietin-1 and Angiopoietin-2, regulate its activation status. Genetic and molecular studies spanning thousands of humans link Tie2 and imbalance of the Angiopoietins to major adverse clinical events arising from bacterial sepsis, other severe infections, and even acute sterile inflammation. Summary: The Tie2 signaling axis may constitute a molecular switch in systemic inflammation that can be measured and manipulated to target the host vascular response therapeutically.